Dinâmicas contemporâneas da migração africana e haitiana para o Brasil - Elie de Montalembert (Confins)
The work aims to study two recent migration flows to Brazil. The first concerns migrants from Haiti, the second migrants from African countries. It aims to dress a typology of these migrations, in order to understand the socio-demographic profile and the routes taken by these people to reach Brazil, while situating these new migratory flows in the context of the history of migration in Brazil. Finally, the aim will be to discuss the prospects for migration in Brazil, in the actual context of the economic crisis and political radicalization in the country.